Determination of transient thermal characteristics for thermal electric behavioral models of integrated circuits - Drakin A. Yu; Potapov L. A.; Shkolin A. N. (Bulletin of Electrical Engineering and Informatics, 2020)
In the current study, it was tried to describe a method for determining thermal characteristics of integrated micro-circuits to identify thermal parameters of multidisciplinary (thermal-electric) behavioral models. The problem is solved on the example of high-frequency pulse voltage converters. A solution was proposed to refine the minimum structure of the thermoelectric model based on an iterative least squares method using the Levenberg-Marquardt  algorithm, as well as a graph of the spectral den-sity of time constants. This made it possible to reduce the influence of the filtering factor in the  deconvolution operation when building a thermal model using the structural function of the thermal characteristic transition. Also, the results obtained can be used to build integrated circuits (IC) behavioral models, taking into account the thermal processes occurring in them.